(untitled) (Advancements in Homeopathic Research, 2022)
Uterine fibroids, also called as Leiomyomas or myomas, are very common benign (non-cancerous) over growths that develop in the muscular wall of the uterus. They can be very tiny to larger than a cricket ball in size. In most of the cases, there is more than one fibroid in the uterus. Some times fibroids can be asymptomatic, but most of the time due to their size and location, fibroids can lead to problems for some women like abdominal pain and heavy bleeding. Rarely they can develop in to cancer. Even though their pathogenesis is not clearly known, there is considerable evidence that estrogen and progesterone proliferate the growth of fibroids, as they rarely appear before menarche and regress after menopause.